2015
DOI: 10.1038/tp.2015.66
|View full text |Cite
|
Sign up to set email alerts
|

The positive effect on ketamine as a priming adjuvant in antidepressant treatment

Abstract: Ketamine is an anesthetic with antidepressant properties. The rapid and lasting effect of ketamine observed in preclinical and clinical research makes it a promising therapeutic to improve current major depression (MD) treatment. Our work intended to evaluate whether the combined use of classic antidepressants (imipramine or fluoxetine) and ketamine would improve the antidepressant response. Using an animal model of depressive-like behavior, we show that the addition of ketamine to antidepressants anticipates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
(49 reference statements)
4
27
0
3
Order By: Relevance
“…[10,15]). Moreover, rodent and human evidence show region-specific neuroplasticity effects of ketamine consistent with increased synaptic connectivity in the PFC and hippocampus, but decreased synaptic connectivity in the nucleus accumbens (NAc) [33,34]. The opposing changes in neuroplasticity were independently related to successful ketamine treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…[10,15]). Moreover, rodent and human evidence show region-specific neuroplasticity effects of ketamine consistent with increased synaptic connectivity in the PFC and hippocampus, but decreased synaptic connectivity in the nucleus accumbens (NAc) [33,34]. The opposing changes in neuroplasticity were independently related to successful ketamine treatment [33].…”
Section: Discussionmentioning
confidence: 99%
“…A recent preclinical study has confirmed that chronic unpredictable stress induces an increase in dendritic length and spine density in the NAc. In addition, the study revealed that ketamine treatment reversed stress-induced neuroplasticity alterations in the NAc (Melo et al, 2015). The question is therefore raised whether these preclinical findings in the NAc would translate into tangible evidence in patients suffering from MDD.…”
Section: Introductionmentioning
confidence: 98%
“…Hippocampal tissue levels of glutamate were measured by HPLC, using a GBC LC1150 (GBC Inc, Braeside, Australia) pump coupled to a BAS LC4C electrochemical detector, after pre-column derivatization. Minor modifications of a previously-described method were used ( Kokras et al, 2009;Melo et al, 2015 ). Briefly, a glass-carbon working electrode (set at + 800 mV), an Ag/AgCl 2 reference electrode, and a Hypersil Gold aQ (150 mm × 2.1 mm, 5 μm, from Thermo Fisher Scientific) were used.…”
Section: Neurochemical Assaysmentioning
confidence: 99%